Detection of myocardial infarction - is it all troponin?: point - Giannitsis, Evangelos; Katus, Hugo (Clinical chemistry, 2012)
Cardiac troponin is a cardiospecific protein that is detectable in the blood of patients with myocardial injury with sensitive and specific assays (1). Cardiac troponin is recommended as the preferred biomarker for the diagnosis of myocardial infarction (MI),2 for risk stratification, and for therapeutic guidance regarding anticoagulation therapy and invasive management (2-4). Assays should be appropriately precise to measure at the 99th-percentile value with a total imprecision of ≤10%. Until recently, assays were insufficiently precise, and rather than using the recommended 99th-percentile value, many clinicians had advocated the use of the lowest value at which an assay achieved a 10% CV as the decision cutoff. Manufacturers have refined their assays through improvements in reagent or antibody configuration, changes in the microparticle capture bed, introduction of a third antibody, increases in sample volume, and other modifications (5). For these reasons, newer generations of cardiac troponin assays now provide improved analytical sensitivity and precision.High-sensitivity cardiac troponin assays have reduced the time from symptom onset to detectable marker increases compared with former assays. Keller et al. (6) demonstrated that a contemporary sensitive cardiac troponin I (cTnI) assay allowed a diagnosis of MI on admission in an acute coronary syndrome (ACS) population with a sensitivity of 90.7% and a negative predictive value (NPV) of 96.4%. A second sample 3 h after symptom onset identified all patients with a final MI diagnosis, irrespective of the time delay from onset of symptoms to presentation. Reichlin et al. (7) evaluated 786 consecutive patients with suspected ACS and demonstrated better performance of 4 cardiac troponin assays more sensitive than the conventional fourth-generation cTnT assay, with sensitivities at presentation of between 84% and 95% (NPVs, 97%-99%). Both trials indicated that the benefits of earlier detection were most pronounced for patients presenting early after chest pain …